(untitled) (Journal of Nematode Morphology and Systematics, 2012)
Two new and four known species of the genus Belondira Thorne, 1939 are described and illustrated. Belondira provulva sp. n. is characterized by its body 0.8-1.1 mm long, odontostyle 5.0-5.5 μm long and with distinct lumen and aperture, odontophore rod-like, expanded part of pharynx occupying 33-37% of neck length, V = 28-32, anterior uterine sac 1.7-2.8 times the corresponding body width long, tail short and clavate with distinct striation, spicules 23-25 μm long and two spaced ventromedian supplements. Belondira wajahati sp. n. is distinguished by having 1.4- 1.6 mm long body, cephalic framework moderately sclerotized, robust odontostyle 5.0-6.0 μm long and with distinct aperture, expanded part of pharynx occupying 56-64% of total neck length, anterior uterine sac 1.5-2.0 times the corresponding body width long, and tail short and hemispheroid. Belondira porta Thorne, 1964, B. paraclava Jairajpuri, 1964, B. syedi Suryawanshi, 1972 and B. microdora Ahmad, Dhanachand & Jairajpuri, 1982 are re-described; and B. porta is reported for the first time from India. A key to species of Belondira is also provided.